(untitled) (Archive of Conferences, 2021)
The article presents the properties of irrigated typical gray soils of the selected pilot sites and considerations on the automation of one of the key links in agriculture - the chemicalization system. The soils prevalent in the republic are formed on horizontal and vertical zonations, which differ in properties not only by soil types, but also by each field contour. Which leads to an improvement in soil fertility and optimization of the balance of nutrients through the introduction of modern technical and technology, the article also provides data on the need to develop modern units specializing in the automatic application of individual mineral fertilizers for each crop, in order to preserve and stimulate the economy of land users, in particular farms and agricultural clusters